Acute navicular fractures: report of two cases and review of the literature - Giaretta, Stefano; Aprato, Alessandro; Anselmi, Angela; Ceretta, Federica; Braggio, Leonardo; Mazzi, Michele; Rebeccato, Arturo (Lo Scalpello - Journal, 2022)
Introduction. The navicular bone is the keystone of the foot medial longitudinal arch and is an active participant in the transverse tarsal locking mechanism. The fusion of the talonavicular joint has been demonstrated to significantly reduce the motion of the subtalar and the calcaneocuboid joint and severely limit the excursion of the posterior tibial tendon. Navicular fractures are quite rare injuries, but, because of the importance of this bone in foot motion, undiagnosed, mismanaged, or delayed diagnosed fractures can cause serious complications. Nowadays, the literature that describes the management of the navicular fractures is limited; open reduction and internal fixation is the gold standard for treatment of navicular fractures, but there is no consensus about the preferred technique to use in these fractures. Case report. Two cases of navicular fracture associated with other mid-foot fracture treated with cerclage are presented. The navicular fractures were fixed with screws and a cable-wire passed circumferentially to the navicular bone through a trochanteric cable passer in order to prevent radial displacement of the fragments. Discussion. Review of the literature analyzing the management of acute navicular fractures including surgical management and post-operative treatment. Conclusions. The use of cerclage with cable-wire and trochanteric cable passer is a good option of treatment for navicular fractures, but the availability of different tools and hardware studied for these fractures can help guide the surgeon to use less invasive and more conservative techniques, such as cerclage, an evolving and easily reproducible technique.